Revealing Employee Experience in Surviving during the COVID-19 Pandemic: Story from Indonesia - Nurus Sa'adah; Elvin Qoumas Muhammad Fahd; Ratna Sesotya Wedadjati; Chusminah (Indigenous: Jurnal Ilmiah Psikologi, 2024)
The covid-19 pandemic has brought diverse experiences to every employee in the company. Several types of research have sought to uncover how the fate of employees in the pandemic is related to company policies. However, no one has explained the concept of employee experience that can explain all components of the experience comprehensively, detailed, and empathize with its employees, especially during this pandemic. This study is field research by distributing questionnaires in google form to twenty employees in various companies in Indonesia. Data analyzed by the triangulation method. During the covid-19 pandemic, almost companies care about the fate of employees, rarely who break their employment or lower compensation. Most pay more attention to employees' positive experiences of the physical environment, technology environment, and cultural environment. The novelty is for Indonesians, employee experience is a positive experience of employees towards the company's internal environment and can be shared with the external community of the company. Employees feel positive experience in the physical, technology, and cultural environment during the COVID-19 pandemic. The research limitation is that it only involves management-level employees, not yet applying all levels of employees who are likely to get more comprehensive information. Nonetheless, the available information is sufficient to enforce the adequate conclusion.